EXPERIMENTAL STUDY OF THE K2ZRSI3O9 (WADEITE)-K2TISI3O9 AND K2(ZR,TI)SI3O9-PHLOGOPITE SYSTEMS AT 2-3 GPA - Orlando A.; Thibault Y.; Edgar A.D. (My University, 2000)
Experiments ranging from 2 to 3 GPa and 800 to 1300°C and at 0.15 GPa and 770°C were performed to investigate the stability and mutual solubility of the K2ZrSi3O9 (wadeite) and K2TiSi3O9 cyclosilicates under upper mantle conditions. The K2ZrSi3O9–K2TiSi3O9 join exhibits complete miscibility in the P–T interval investigated. With increasing degree of melting the solid solution becomes progressively enriched in Zr, indicating that K2ZrSi3O9 is the more refractory end member. At 2GPa, in the more complex K2ZrSi3O9–K2TiSi3O9–K2Mg6Al2Si6O20(OH)4 system, the presence of phlogopite clearly limits the extent of solid solution of the cyclosilicate to more Zr-rich compositions [Zr/(Zr+Ti)>0.85], comparable to wadeite found in nature, with TiO2 partitioning strongly into the coexisting mica and/or liquid. However, at 1200°C, with increasing pressure from 2 to 3GPa, the partitioning behaviour of TiO2 changes in favour of the cyclosilicate, with Zr/(Zr+Ti) of the K2(Zr,Ti)Si3O9 phase decreasing from ~0.9 to ~0.6. The variation in the Ti content of the coexisting phlogopite is related to its degree of melting to forsterite and liquid, following the major substitution VITi+VI□=2VIMg.